2017
DOI: 10.1002/ceas.12059
|View full text |Cite
|
Sign up to set email alerts
|

Expert Supervisors' Priorities When Working With Easy and Challenging Supervisees

Abstract: Using Kemer, Borders, and Willse's (2014) concept map as a conceptual model, the authors aimed to understand expert supervisors' priorities with their easy and challenging supervisees. Experts' priorities with easy and challenging supervisees were represented in different parts of the concept map, and they seemed to individualize their work with challenging supervisees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…To offer more data‐driven understandings of how expert supervisors develop their practices, researchers have examined exceptional supervisors in the specific domain of clinical supervision using nominations, peer identification, and academic criteria. In several studies, researchers (e.g., Grant, Schofield, & Crawford, 2012; Kemer, Borders, & Yel, 2017; Nelson, Barnes, Evans, & Triggiano, 2008) found that expert supervisors paid acute attention to the supervisory relationship and were willing to be direct and to confront when necessary, even if they were uncomfortable doing so. Expert supervisors increased their efforts to gather data and understand their supervisees’ dilemmas, had ongoing reflections on their work both during and between supervision sessions, and critically examined their current approaches to supervision.…”
mentioning
confidence: 99%
“…To offer more data‐driven understandings of how expert supervisors develop their practices, researchers have examined exceptional supervisors in the specific domain of clinical supervision using nominations, peer identification, and academic criteria. In several studies, researchers (e.g., Grant, Schofield, & Crawford, 2012; Kemer, Borders, & Yel, 2017; Nelson, Barnes, Evans, & Triggiano, 2008) found that expert supervisors paid acute attention to the supervisory relationship and were willing to be direct and to confront when necessary, even if they were uncomfortable doing so. Expert supervisors increased their efforts to gather data and understand their supervisees’ dilemmas, had ongoing reflections on their work both during and between supervision sessions, and critically examined their current approaches to supervision.…”
mentioning
confidence: 99%
“…In Kemer et al's study (2014), one of the five areas of expert clinical supervisors' supervision thoughts was their selfassessment and reflection, including awareness of their own feelings and biases. Expert supervisors in other studies also prioritized and used self-assessment and reflection in challenging supervisory situations (e.g., Grant et al, 2012;Kemer et al, 2017). Thus, experts'…”
Section: Discussionmentioning
confidence: 99%
“…The most recent literature demonstrates substantial depth in research regarding elements of the supervision process, most often with engagement of active stakeholders and use of content analysis. This area included classification of expert site supervisors’ cognitions during supervision (Kemer, Pope, & Neuer Colburn, 2017), descriptions of easy and challenging supervisees (Kemer & Borders, 2017), and priorities with easy and challenging supervisees (Kemer, Borders, & Yel, 2017). There were broadscale accounts of most and least helpful events in individual, triadic, and group supervision (Fickling, Borders, Mobley, & Wester, 2017) and more in‐depth exploration of challenging supervisory issues, including providing corrective feedback (Borders, Welfare, Sackett, & Cashwell, 2017), nondisclosure in triadic supervision (Lonn & Juhnke, 2017), power dynamics within the supervisory relationship (De Stefano, Hutman, & Gazzola, 2017), and feedback exchanged in group supervision (Wahesh, Kemer, Willis, & Schmidt, 2017).…”
Section: Supervisionmentioning
confidence: 99%